Prevalence of Chronic Kidney Disease, Its Risk Factors and Outcome in Nepal: A Systematic Review and Meta-analysis - Shrestha, Dhan Bahadur; Budhathoki, Pravash; Sedhai, Yub Raj; Baniya, Ramkaji; Gaire, Suman; Adhikari, Yuvraj; Marasini, Anupama; Bhandari, Shakar; Sedhain, Arun (Journal of Nepal Health Research Council, 2021)
Background: Hypertension, diabetes, glomerulonephritis, obesity, and family history of kidney diseases are major risk factors for chronic kidney disease. Due to the paucity of data on a national level regarding the prevalence, risk factors, and complications of chronic kidney disease, we performed this meta-analysis. Methods: We searched online databases from January 2000 till October 2020. Two reviewers screened articles using Covidence software. Comprehensive Meta-Analysis Software version 3 was used for data analysis.Results: Among chronic kidney disease patients, 35.96% were found to have high LDL, 34.22% had hypercholesterolemia, 39.18% had hypertriglyceridemia, and 42.23% had low HDL. Pigmentary changes were reported in 37.71%, pruritus in 30.96%; and xerosis in 48.55%. Among the reported nail problems, the brown nail was reported in 7.19%, half and half nail in 6.07%, and white nail in 20.65%.Conclusions: The prevalence of chronic kidney disease among high-risk cohorts in Nepal was significant among risk group with hypertension and diabetes being the most common risk factors. The most common stage of chronic kidney disease was Stage V, and the common complications were skin problems and dyslipidemia.Keywords: Diabetes mellitus; glomerulonephritis; hypercholesterolemia; hypertension; hypertriglyceridemia; renal insufficiency chronic; risk factors